Vegetable storage practices and the reproduction of household autonomy in early village contexts from northwest Argentina - Molar Becchio, Rocío María (2018)
Storage is an extended and variable practice which constitutes a key aspect for understanding economic strategies, social structures, and political negotiations in different cultural and temporal settings, but especially in the context of early village societies. Despite the fact that it was traditionally addressed as an evidence of the emergence of elites with the power to hoard and redistribute social surpluses, we herein address the role of storage where this social consequence was not recorded. We present new archaeological data on Tafí valley early village vegetable storage practices which is interpreted in the light of the ethnoarchaeological study case of household storage features, pirhuas, still used by Diaguita peasants from the nearby Anfama valley. Domestic and productive architectural features, pottery assemblages and botanical microremains were analyzed in order to discuss surplus generation, vegetable products control and household autonomy in the context of South Andean early villages.